2021
DOI: 10.3390/psychiatryint2030023
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Restraint Behavior, Stigma and Depressive Tendency in Office Workers during the COVID-19 Pandemic in Japan—Self-Restraint Behavior and Depression during the COVID-19

Abstract: Background: The COVID-19 pandemic has forced people to change their lifestyles, especially with respect to restrictions on going out. Forced quarantine (i.e., lockdown) and self-restraint behavior (SRB), including self-quarantine, are suggested to induce potential negative impacts on public mental health. SRB seems to be related to governmental policies, each individual’s social background and mental condition; however, no empirical studies have been conducted. Methods: 1053 participants (mainly office workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…(2) Variables affecting SRB For SRB, motivation for SRB led to actual SRB six months later, consistent with previous research showing that motivation for SRB influences actual changes in outgoing behavior (Katsuki et al, 2021). Furthermore, the present results suggest that SRB may have been caused not only by awareness of the social change of the novel COVID-19 pandemic, but also by lack of socialization and complaints, as well as an original tendency toward isolation, which led to retreat from interpersonal relationships and consequently resulting in SRB.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…(2) Variables affecting SRB For SRB, motivation for SRB led to actual SRB six months later, consistent with previous research showing that motivation for SRB influences actual changes in outgoing behavior (Katsuki et al, 2021). Furthermore, the present results suggest that SRB may have been caused not only by awareness of the social change of the novel COVID-19 pandemic, but also by lack of socialization and complaints, as well as an original tendency toward isolation, which led to retreat from interpersonal relationships and consequently resulting in SRB.…”
Section: Discussionsupporting
confidence: 82%
“…DWLS is recommended when non-normal or categorical data are included in the observed variables (Toyoda, 2014). The results showed a factor structure consistent with previous studies (Katsuki et al, 2021) as shown in Table 2 (χ 2 (480) = 3532.99, p < 0.01, CFI = 0.87, TLI = 0.86, RMSEA = 0.09, SRMR = 0.11). The Internal consistencies (Cronbach's alpha) for the factors ranged from 0.72 (COVID-19-related stigma) to 0.86 (COVID-19-related depressive feelings).…”
Section: Statisticssupporting
confidence: 88%
See 3 more Smart Citations